2023
DOI: 10.1002/jhet.4646
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic CoCeO2 oxide nanoparticles: An efficient and reusable heterogeneous catalyst for the preparation of 2‐amino‐3‐cyano‐4H‐pyran derivatives

Abstract: CoCeO2 NPs were successfully synthesized and confirmed using x‐ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and high‐resolution transmission electron microscopy (HRTEM) techniques. The catalytic performance of the synthesized CoCeO2 NPs catalyst was examined during the one‐pot multicomponent synthesis of biologically significant 2‐amino‐3‐cyano‐4H‐pyran derivatives. The reaction was easily accomplished using a one‐pot, three‐component reaction of dimedone, aryl aldehydes, and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…From the literature survey, it has been found that there are several methods already reported for the synthesis of ACCs, for examples, Lewis acid‐base based catalysts, organo‐catalysts, homogeneous as well as heterogeneous catalysts such as DBU, [33] L‐proline, [34] piperazine, [35] triethylamine, [36] K 2 CO 3 , [37] triethylammonium hydrogen sulfate, [38] BF 3 .SiO 2 , [39] 2,2,2‐trifluoroethanol (TFE), [40] choline chloride urea, [41] RGO‐SO 3 H, [42] [bmim]OH, [43] CoCeO 2 NPs, [44] ZIF@ZnTiO 3 , [45] thiourea dioxide [46] etc. Only recently study on the multicomponent synthesis of ACCs using a homogeneous cis ‐[Mo VI O 2 ] complex as catalyst has been reported in the literature, [47] while two other studies have considered heterogeneous Fe 3 O 4 ‐supported molybdenum nano catalysts for this synthesis [48,49] …”
Section: Introductionmentioning
confidence: 99%
“…From the literature survey, it has been found that there are several methods already reported for the synthesis of ACCs, for examples, Lewis acid‐base based catalysts, organo‐catalysts, homogeneous as well as heterogeneous catalysts such as DBU, [33] L‐proline, [34] piperazine, [35] triethylamine, [36] K 2 CO 3 , [37] triethylammonium hydrogen sulfate, [38] BF 3 .SiO 2 , [39] 2,2,2‐trifluoroethanol (TFE), [40] choline chloride urea, [41] RGO‐SO 3 H, [42] [bmim]OH, [43] CoCeO 2 NPs, [44] ZIF@ZnTiO 3 , [45] thiourea dioxide [46] etc. Only recently study on the multicomponent synthesis of ACCs using a homogeneous cis ‐[Mo VI O 2 ] complex as catalyst has been reported in the literature, [47] while two other studies have considered heterogeneous Fe 3 O 4 ‐supported molybdenum nano catalysts for this synthesis [48,49] …”
Section: Introductionmentioning
confidence: 99%